Biogenic synthesis of selenium nanoparticles and their effect on as(III)-induced toxicity on human lymphocytes - Prasad, Kumar Suranjit; Selvaraj, Kaliaperumal (Biological Trace Element Research, 2014)
{A bioreductive capacity of a plant, Terminalia arjuna leaf extract, was utilized for preparation of selenium nanoparticles. The leaf extract worked as good capping as well as stabilizing agent and facilitated the formation of stable colloidal nanoparticles. Resulting nanoparticles were characterized using UV-Vis spectrophotometer, transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction analysis (XRD), respectively. The colloidal solution showed the absorption maximum at 390 nm while TEM and selected area electron diffraction (SAED) indicated the formation of polydispersed, crystalline selenium nanoparticles of size raging from 10 to 80 nm. FT-IR analysis suggested the involvement of O-H, N-H
Keywords: Arsenite; Comet assay; EDAX; MTT assay; Selenium nanoparticles; Terminalia arjuna